Identifying elements of mushroom business development in Malang City with a Canvas model approach - Novi Haryati; Paramyta Nila Permanasari; Ardaneswari Dyah Pitaloka Citraresmi (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
The mushroom agroindustry has a profitable business opportunity for farmers because it is easy to cultivate, needs short planting time, and does not require extensive planting land. Moreover, the price of post-harvest products is quite high. To face increasingly intense competition, mushroom agroindustry actors need to implement strategic management to increase business competitiveness. The purposes of this study are to identify a business model using the business mode canvas (BMC) approach, analyse the internal and external factors of mushroom agroindustry and formulate alternative business development strategies using SWOT analysis. The result shows that the business model of mushroom agroindustry viewed by nine elements of BMC. By SWOT analysis, mushroom agroindustry has internal strength in its business that is on clear consumer segmentation (0.650). The weakness is anticipating the fewer consumers’ enthusiasm toward healthy food products (0.500). The opportunity of mushroom agroindustry is optimizing the online market (1.200). The threat is competitors from other food products (0.525). Some alternatives of developing the business are based on hold and maintain position consists of four combined strategies: developing and increasing product quality (SO), increasing promotion and services (ST), marketing the products by social media (WO), and evaluating the quality of business relationship (WT).